2023
DOI: 10.11594/jtls.13.01.20
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Cytotoxic and Antimicrobial Properties of Xanthones from Cratoxylum cochinchinense

Abstract: Cratoxylum cochinchinenseis a perennial plant found in Southeast Asia, having di-verse terminologies in various Southeast Asian countries. It has been traditionally used as medicine, tea and food spice until today. Its phytochemical analysis reveals a rich array of bioactive compounds in different parts of the plant, specifically xan-thones, which are scientifically determined to be the most abundant secondary me-tabolites in C. cochinchinense. Xanthones do possess numerous beneficial properties and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Finding selective drugs with low toxicity to normal cells that are not Pgp substrates may thus be one of the ways to effectively treat this disease. Several studies concerning the evaluation of the biologic activity of xanthones demonstrated that they often present anti-tumor activity [13,[30][31][32], besides many other interesting biological activities, including anti-oxidant, anti-inflammatory, anti-allergy, anti-bacterial, anti-fungal, and anti-viral activities [12,33,34]. Some cell targets for xanthone derivatives have already been described and include, among others, cyclin dependent kinases, important in cell cycle control [35,36], cytokines, kinases that modulate the activity of PI3K, Akt, and TOR proteins or proteins involved in apoptosis, like Bax, Bcl-2, or caspase 3 [37].…”
Section: Effect Of Chiral Derivatives Of Xanthones On the Growth Of H...mentioning
confidence: 99%
“…Finding selective drugs with low toxicity to normal cells that are not Pgp substrates may thus be one of the ways to effectively treat this disease. Several studies concerning the evaluation of the biologic activity of xanthones demonstrated that they often present anti-tumor activity [13,[30][31][32], besides many other interesting biological activities, including anti-oxidant, anti-inflammatory, anti-allergy, anti-bacterial, anti-fungal, and anti-viral activities [12,33,34]. Some cell targets for xanthone derivatives have already been described and include, among others, cyclin dependent kinases, important in cell cycle control [35,36], cytokines, kinases that modulate the activity of PI3K, Akt, and TOR proteins or proteins involved in apoptosis, like Bax, Bcl-2, or caspase 3 [37].…”
Section: Effect Of Chiral Derivatives Of Xanthones On the Growth Of H...mentioning
confidence: 99%
“…Nevertheless, their unique structures inspire the design of new analogues with similar biological actions. Among the natural products with different therapeutic uses, xanthone derivatives, representing a great diversity of compounds, possess a broad spectrum of biological and pharmacological activities [ 2 , 3 , 4 , 5 ], such as anticancer [ 6 , 7 ], antimicrobial [ 8 , 9 ], and anti-inflammatory [ 10 , 11 ] activities. For example, disease-preventative and therapeutic properties of mangosteen ( Garcinia mangostana ), also known as the “queen of fruits”, have been ascribed to xanthone derivatives that are present in several parts of the tree, including the pericarp, fruit rind, peel, stem bark, root bark, and leaf [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1. H NMR (400.14 MHz, DMSO-d 6 ): δ = 8.46 (1H, d, J = 7.8 Hz, N-H), 8.18 (1H, dd, J = 8.0 and 1 5. Hz, H-8), 8.13 (1H, d, J = 8 7.…”
mentioning
confidence: 99%